2017
DOI: 10.1002/adma.201701146
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Gold Nanoparticles Synthesized on Protein Particle Scaffolds for Cancer Theragnosis

Abstract: Cancer theragnosis using a single multimodality agent is the next mainstay of modern cancer diagnosis, treatment, and management, but a clinically feasible agent with in vivo cancer targeting and theragnostic efficacy has not yet been developed. A new type of cancer theragnostic agent is reported, based on gold magnetism that is induced on a cancer-targeting protein particle carrier. Superparamagnetic gold-nanoparticle clusters (named SPAuNCs) are synthesized on a viral capsid particle that is engineered to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 52 publications
1
47
0
1
Order By: Relevance
“…Considering magnetite, despite the reported biocompatibility, it has been shown that these nanoparticles are sensitive to oxidation, being transformed into maghemite in the presence of oxygen [ 59 ]. Moreover, it has been described that iron oxide nanoparticles induce the production of reactive oxygen species in mammalian cells [ 60 ], causing severe DNA and protein damage and inflammatory responses [ 61 , 62 ]. Therefore, magnesium ferrite nanoparticles can be advantageous, avoiding these undesirable effects.…”
Section: Resultsmentioning
confidence: 99%
“…Considering magnetite, despite the reported biocompatibility, it has been shown that these nanoparticles are sensitive to oxidation, being transformed into maghemite in the presence of oxygen [ 59 ]. Moreover, it has been described that iron oxide nanoparticles induce the production of reactive oxygen species in mammalian cells [ 60 ], causing severe DNA and protein damage and inflammatory responses [ 61 , 62 ]. Therefore, magnesium ferrite nanoparticles can be advantageous, avoiding these undesirable effects.…”
Section: Resultsmentioning
confidence: 99%
“…As such, high postoperative recurrence rates may occur with serious operative complications, resulting in organ dysfunction, failure, or even death. [207,211,212] The key advantage of nano-based contrast agents for preoperative imaging is enhanced sensitivity and prolonged circulation time, which allows repeated imaging with only one administration. However, the limited tissue penetration depth and narrow scope of imaging of these technologies at the cellular or tissue level are not suitable for preoperative applications.…”
Section: Preoperative Imaging For Precision Surgerymentioning
confidence: 99%
“…Such fascination with these types of nanoparticles can be explained by their magnetic properties, corresponding to the major requirements of biomedical applications, such as low production cost, good physical and chemical stability, biocompatibility and environmental safety, thus being widely used in target drug delivery, MRI, magnetic hyperthermia and biosensing [ 52 ]. However, it has been reported that iron oxide nanoparticles show peroxidase-like activity, thereby producing reactive oxygen species that may cause severe damage to cell components and induce inflammatory responses [ 53 , 54 , 55 ]. In addition, they tend to accumulate in organs with a high concentration of macrophages and thus may not be advisable for long-term applications such as MRI, taking into consideration that they might disturb the immune function of the reticuloendothelial system [ 53 ].…”
Section: Properties and Applications Of Magnetogelsmentioning
confidence: 99%
“…However, it has been reported that iron oxide nanoparticles show peroxidase-like activity, thereby producing reactive oxygen species that may cause severe damage to cell components and induce inflammatory responses [ 53 , 54 , 55 ]. In addition, they tend to accumulate in organs with a high concentration of macrophages and thus may not be advisable for long-term applications such as MRI, taking into consideration that they might disturb the immune function of the reticuloendothelial system [ 53 ]. Therefore, the use of iron oxide nanoparticles requires improved coating, either polymeric or inorganic, to reduce these effects, which is expected to be more frequent in future reports, as the techniques of production become cheaper and simpler.…”
Section: Properties and Applications Of Magnetogelsmentioning
confidence: 99%